Influence of animal age and breeding activity on carcass traits, meat quality, and sensory attributes of bison bulls - O’Sullivan, Lydia M.; Newton, Clay J.; Underwood, Keith R.; Grubbs, Judson K.; Bakker, Christina E.; Cammack, Kristi M.; Dinh, Thu; Kruse, Carter; Blair, Amanda D. (Frontiers in Ecology and Evolution, 2026)
In the bison industry, both heifers and bulls are marketed and harvested at various ages, generally ranging from 20 to 30 months. Bulls represent the greatest proportion of the slaughter mix, as the bison industry does not routinely castrate, leaving males intact throughout the growing and finishing phase. This practice makes bulls available for use during the breeding season prior to the finishing phase. Therefore, the objective of this study was to evaluate the influence of bull age and use in the breeding herd on carcass characteristics, meat quality, and sensory characteristics of bison bulls. Grass-finished bison bulls were assigned to one of two finishing treatments: 1) Young bulls (n = 98) finished on fall pasture and harvested at 30 months of age with no exposure to the breeding herd, or 2) Mature bulls (n = 24) finished on early summer pasture and harvested at 36 months of age following use in the breeding herd. Bison were harvested, carcass data were recorded, and striploins were collected for the analysis of meat quality attributes. Mature bulls had greater hot carcass weight, ribeye area, kidney fat percentage, and marbling score compared to Young bulls. Objective tenderness was affected by the interaction of postmortem aging and finishing treatment. Steaks from Young bison bulls were more tender at all aging time points compared to steaks from Mature bison bulls. Variation in tenderness between treatment groups was likely not due to differences in collagen, as total collagen was greater in steaks from Young bulls. Consumer panelists rated steaks from Mature bulls higher for toughness intensity and flavor liking and lower for off-flavor intensity. Trained panelists rated steaks from Young bulls higher for flavor intensity, while ratings for toughness and juiciness were increased for Mature bulls. Collectively, results from this study indicate that bulls used in the breeding herd and marketed at 36 months of age produced heavier carcasses. However, Mature bulls were tougher at all postmortem aging days and required 21 days of aging to reach an acceptable level of tenderness, which was detected by both trained and consumer panelists.